2009
DOI: 10.1007/s00248-009-9493-0
|View full text |Cite
|
Sign up to set email alerts
|

1-Aminocyclopropane-1-Carboxylate (ACC) Deaminase Genes in Rhizobia from Southern Saskatchewan

Abstract: In Table 1 of the original version of this article, there were mistakes on the Accession numbers under the third column "ACC deaminase gene". Correct Table 1 is given here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…strains, among 233 rhizobial strains obtained from 30 different sites across Saskatchewan, Canada, displayed ACC deaminase activity (Duan et al, 2009). Ahmad et al (2011) isolated ten rhizobia and 25 PGPR containing ACC deaminse from nodules and rhizosphere soil samples of mungbean.…”
Section: Resultsmentioning
confidence: 99%
“…strains, among 233 rhizobial strains obtained from 30 different sites across Saskatchewan, Canada, displayed ACC deaminase activity (Duan et al, 2009). Ahmad et al (2011) isolated ten rhizobia and 25 PGPR containing ACC deaminse from nodules and rhizosphere soil samples of mungbean.…”
Section: Resultsmentioning
confidence: 99%
“…ACC deaminase induction in cells was performed as described by Duan et al (2008). Mesorhizobium strains were grown in TY (supplemented with 20 μg/ ml tetracycline when necessary) for 2-3 days at 28°C.…”
Section: Acc Deaminase Activity Assaymentioning
confidence: 99%
“…Thus, the rhizobacteria diminish the accumulation of excess ethylene levels and re-establish a healthy root system to deal with environmental stress. The study of rhizospheric bacteria such as Bacillus, Enterobacter, Pseudomonas, and Rhizobium, which have ACC deaminase activity (Duan et al, 2009), has demonstrated the expression of the ACC deaminase gene in plants under environmental stress treated with PGPR. Enterobacter cloacae and Pseudomonas putida expressing ACC deaminase have been associated with an increase in resistance to stress in inoculated tomato seeds (Glick, 2004).…”
Section: Production Of 1-amino Cyclopropane-1-carboxylic Acid (Acc) Dmentioning
confidence: 99%